Exploration on Issues Related to Welfare of Medical Personnel in Grassroots Hospitals: Physician Welfare in Primary Hospitals - Gao, Junchen; Zhang, Jian; Lv, Moqi; Ge, Pan; Yang, Yanqi; Zhang, Nan; Zhou, Dangxia (Serican Journal of Medicine, 2024)
Grassroots hospitals, like other medical service institutions, are public welfare undertakings that the government provides services to the people. Because of its own close to home, quick medical treatment, good effect, grassroots hospitals has an important role in the treatment of small diseases. However, this feature also brings the drawbacks of heavy tasks, low pay and low status for medical workers, which directly lead to the difficulties in the introduction of outstanding talents and the loss of current workers. In view of this situation, this paper discusses how to supplement the existing programs to solve these problems through literature comparison, puts forward the program of improving welfare benefits, and bring views on the existing problems and how to further improve the living standards of grass-roots doctors